Heterocyclic organobismuth (III) compounds containing an eight-membered ring: Inhibitory effects on cell cycle progression. (August 2018) - Iuchi, Katsuya; Yagura, Tatsuo
Abstract: We previously showed that heterocyclic organobismuth compounds have excellent antimicrobial and antitumor potential. These compounds structurally consist of either six- or eight-membered rings. Previous research has shown that bi-chlorodibenzo[ c, f ][1, 5]thiabismocine (Compound 3), an eight-membered ring, induced G2 /M arrest via inhibition of tubulin polymerization in HeLa cells. Additionally, N - tert -butyl-bi-chlorodi-benzo[ c, f ][1, 5]azabismocine (Compound 1), another eight-membered ring, exhibited higher cytotoxicity than Compound 3 against several cancer cell lines, including HeLa and K562. Finally, bi-chlorophenothiabismin- S, S -dioxide (Compound 5), a six-membered ring, exhibited lower antitumor activity than eight-membered ring compounds. In this study, we investigated the antimitotic activity of Compounds 1 and 5 in HeLa cells. At low concentrations, (0.1 and 0.25 μM), Compound 1 inhibited cell growth and arrested the cell cycle in mitosis. However, 0.5 μM Compound 1 exhibited no antimitotic activity. Conversely, Compound 5 weakly inhibited cell growth and did not markedly arrest the cell cycle. Flow cytometry showed that Compound 1 arrested the cell cycle at G2 /M, resulting in apoptosis. Compound 1 inhibited tubulin polymerization as revealed by a cell-free assay, and both Compounds 1 and 3 inhibited microtubule spindle formation and chromosome alignment during prometaphase. These results suggest that eight-membered ring-containing organobismuth compounds can induce mitotic arrest by perturbing spindle dynamics. Highlights: Eight-membered ring organobismuth compounds induce mitotic arrest. Six-membered ring organobismuth compound exhibits weak antimitotic activity. Eight-membered ring organobismuth compounds induce perturbation in spindle dynamics.